2020
DOI: 10.1002/jid.3515
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Data During an Epidemic: A Novel Mobile Phone Research Method

Abstract: This study developed a data collection method, combining (i) random‐digit dialling and interactive voice response to sample and screen respondents and (ii) computer‐assisted telephone interviewing, to survey 2265 respondents during the 2014 Ebola epidemic. The response, cooperation, refusal and contact rates computed according to the American Association for Public Opinion Research were 51.97, 52.62, 41.85 and 98.77 per cent, for interactive voice response and 91.10, 91.65, 8.30 and 99.40 per cent for computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Additional challenges in health crises often include underlying institutional mistrust and misinformation (Vinck et al, 2019) and logistical obstacles to needs assessments and outreach with vulnerable populations (Checchi et al, 2017). In this context, we demonstrate simple interventions that can complement phone data collection during epidemics Maffioli, 2020;Magaço et al, 2021). In particular, our Teaching intervention shows that providing feedback on knowledge-based questions is a feasible and impactful add-on to health surveys-for example, on "knowledge, attitudes, and practices (KAP)" surveys common in public health.…”
Section: Introductionmentioning
confidence: 90%
“…Additional challenges in health crises often include underlying institutional mistrust and misinformation (Vinck et al, 2019) and logistical obstacles to needs assessments and outreach with vulnerable populations (Checchi et al, 2017). In this context, we demonstrate simple interventions that can complement phone data collection during epidemics Maffioli, 2020;Magaço et al, 2021). In particular, our Teaching intervention shows that providing feedback on knowledge-based questions is a feasible and impactful add-on to health surveys-for example, on "knowledge, attitudes, and practices (KAP)" surveys common in public health.…”
Section: Introductionmentioning
confidence: 90%
“…Data used in this study come from individual telephonic surveys with male migrants from three states in India – Bihar, Uttar Pradesh (UP), and West Bengal (WB). 1 This mode of data collection is becoming increasingly popular and has been previously used by Maffioli (2020) to survey respondents during an Ebola epidemic in Liberia in 2014 and more recently by Allen et al (2021) to study the economic and educational impact of COVID-19 in Mozambique. 2…”
Section: Data and Variables Of Interestmentioning
confidence: 99%
“…For example, in a phone survey on voting behavior in Nigeria, Lau et al (2019) found 0.2% and 3% response rates for SMS and IVR surveys, respectively. In contrast, in Ghana and Liberia, researchers used IVR surveys to screen valid phone numbers from a list of randomly generated numbers and found response rates of 31% and 52%, respectively (L'Engle et al, 2018;Maffioli, 2020). In Burkina Faso, a "hybrid IVR survey" that involved a real person introducing the survey before the automated calls were launched yielded a response rate of nearly 20% (Greenleaf et al, 2020).…”
Section: Evidence On Relative Effectiveness Of Survey Modes In Follow...mentioning
confidence: 99%